The power of linked data: Evaluating diverse multi-program projects designed to reduce welfare dependence - Povey, Jenny; Baxter, Janeen; Ambrey, Christopher; Kalb, Guyonne; Ribar, David; Western, Mark (International Journal of Population Data Science, 2018)
This presentation showcases the innovative use of linked government administrative data in Australia to evaluate a range of diverse social interventions aimed at supporting vulnerable groups to achieve economic independence. The interventions were developed and funded as part of the Australian Priority Investment Approach to Welfare, an approach supported by actuarial analyses of administrative data designed to deliver targeted support for groups at-risk of long-term welfare dependence. In 2018, the Australian Government, commissioned an impact evaluation to assess the effectiveness of the approach in achieving its intended outcomes. The evaluation is based on analyses of linked administrative data to assess the extent to which the new interventions enabled pathways out of welfare dependence. Our presentation will outline the strengths and weaknesses of using government administrative data to evaluate the outcomes. Strengths include easy comparison across diverse programs designed to achieve the same goals; reduced respondent reporting burdens; robust quasi-experimental techniques such as a matching design based on exact matching on a few key characteristics and/or propensity score matching on a broad range of pre-program characteristics; and evidence-based investment practice decisions. Weaknesses include the adoption of an observational rather than experimental design and the lack of information on some social characteristics such as orientations to work, attitudes and social values. The presentation not only assesses the compilation of administrative data used for the first time to evaluate multi-program projects, it will also describe how these data feed into visual interactive dashboards used to monitor the outcomes of the interventions.